Principles of bone regeneration - Bab, Itai A.; Sela, Jona J. (Springer US, 2012)
Principles of Bone Regeneration is a timely publication that addresses the modern aspects of bone healing and repair. This exciting new volume details the convergence of the different experimental and clinical approaches designed for the study and treatment of bone healing in its diverse forms and under varying conditions. Bone healing is affected by a multitude of genetic, environmental, mechanical, cellular and endocrine variables which eventually lead to changes in gene expression that enhance the guided action of osteoblasts (and chondroblasts) to lay down bone that restores, or even improves, the skeletal load bearing capacity. Recent breakthroughs in understanding the regulatory aspects of bone formation and resorption, in both research and clinical arenas offer new modalities to induce, enhances and guide repair processes in bone for the benefit of millions of patients with conditions such as nonunion fractures, critical size defects, orthodontic tooth movement, periodontal bone loss, intraosseous implants and deformed bones.